Design and Fabrication of Fibrous Nanomaterials Using Pull Spinning. Issue 3 (17th January 2017) - Deravi, Leila F.; Sinatra, Nina R.; Chantre, Christophe O.; Nesmith, Alexander P.; Yuan, Hongyan; Deravi, Sahm K.; Goss, Josue A.; MacQueen, Luke A.; Badrossamy, Mohammad R.; Gonzalez, Grant M.; Phillips, Michael D.; Parker, Kevin Kit
Abstract : Pull spinning is a compact, portable nanofiber fabrication system that rapidly produces natural and synthetic fibers with minimal external processing parameters. Numerical, mechanical, and imaging analysis confirms pull spinning's ability to produce defect‐free nanofibers with controllable orientation. The efficacy of point‐of‐use pull spun nanofibers is demonstrated for three case studies, ranging from tissue engineering to point‐of‐wear apparel. Abstract : The assembly of natural and synthetic polymers into fibrous nanomaterials has applications ranging from textiles, tissue engineering, photonics, and catalysis. However, rapid manufacturing of these materials is challenging, as the state of the art in nanofiber assembly remains limited by factors such as solution polarity, production rate, applied electric fields, or temperature. Here, the design and development of a rapid nanofiber manufacturing system termed pull spinning is described. Pull spinning is compact and portable, consisting of a high‐speed rotating bristle that dips into a polymer or protein reservoir and pulls a droplet from solution into a nanofiber. When multiple layers of nanofibers are collected, they form a nonwoven network whose composition, orientation, and function can be adapted to multiple applications. The capability of pull spinning to function as a rapid, point‐of‐use fiber manufacturing platform is demonstrated for both muscle tissue engineering and textile design.